Evaluasi Kebijakan Pajak Progresif Untuk Kendaraan Bermotor Di Kabupeten Gowa : Dampak Dan Tantangan - Arfah, Dwi Astuty; Amril, Amril; Karmila, Yusri (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
This research aims to evaluate the implementation of progressive motor vehicle tax policy in Gowa Regency, focusing on the impacts and challenges faced in its implementation. The method used in this research is qualitative with a descriptive approach. Data was collected through in-depth interviews with relevant parties, including Samsat employees, policy observers, and the public as taxpayers. The results show that the progressive tax policy has a positive impact on increasing local revenue as well as being an instrument to control the growth of private vehicles. However, its implementation still faces a number of obstacles, including the lack of integrated data systems between agencies, low public understanding of the policy, and the lack of adequate public transportation infrastructure. In addition, there are tax evasion practices carried out by some people. This study recommends the need for increased data integration, more intensive socialization, simplification of payment procedures, and development of public transportation as an effort to support the success of the policy. The findings are expected to be an input for local governments in formulating strategies to improve progressive tax policies in the future.